A novel JAK inhibitor, peficitinib, demonstrates potent efficacy in a rat adjuvant-induced arthritis model - Misato Ito; Shunji Yamazaki; Kaoru Yamagami; Masako Kuno; Yoshiaki Morita; Kenji Okuma; Koji Nakamura; Noboru Chida; Masamichi Inami; Takayuki Inoue; Shohei Shirakami; Yasuyuki Higashi (Elsevier, 2017)
The Janus kinase (JAK) family of tyrosine kinases is associated with various cytokine receptors. JAK1 and JAK3 play particularly important roles in the immune response, and their inhibition is expected to provide targeted immune modulation. Several oral JAK inhibitors have recently been developed for treating autoimmune diseases, including rheumatoid arthritis (RA). Here, we investigated the pharmacological effects of peficitinib (formerly known as ASP015K), a novel, chemically synthesized JAK inhibitor. We found that peficitinib inhibited JAK1 and JAK3 with 50% inhibitory concentrations of 3.9 and 0.7 nM, respectively. Peficitinib also inhibited IL-2-dependent T cell proliferation in vitro and STAT5 phosphorylation in vitro and ex vivo. Furthermore, peficitinib dose-dependently suppressed bone destruction and paw swelling in an adjuvant-induced arthritis model in rats via prophylactic or therapeutic oral dosing regimens. Peficitinib also showed efficacy in the model by continuous intraperitoneal infusion. Area under the concentration versus time curve (AUC) at 50% inhibition of paw swelling via intraperitoneal infusion was similar to exposure levels of AUC at 50% inhibition via oral administration, implying that AUC might be important for determining the therapeutic efficacy of peficitinib. These data suggest that peficitinib has therapeutic potential for the oral treatment of RA.